GENOCIDE: CAUSES BEHIND A GRAVEST STATE CRIME - Syed Enam Ahammad (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
This article will investigate the underlying conditions that make genocide possible, analysing the facts, examining how and why human beings are capable of such criminal action. Throughout the history many intellects including Raphael Lempkin (1944) came up with the definition for the term genocide. Genocide is understood as the gravest crime that is possible to commit against humanity. This is a deliberate action to destroy an ethnic, national, racial or religious group in whole or in part. Genocide is not simply unjust, but it is also evil. It is referred to mass murder that is usually carried out by a state or group, caused by many conflicts and tensions between various sects’ overtime and lead to anxiety that turns into mass murder. The reason for such crime against humanity can vary from people to people - such as, to gain power, greed, political influence, vengeance or religious reasons. It is characteristics, includes the one-sided killing of defenceless civilians. Furthermore, it will explain the unique cases and patterns of genocide along with Stanton's discussion of the ten stages that lead to a state or an individual to carry out the mass killing. Also, it will discuss the negative propaganda of governments and groups that cause division amongst communities. Finally, it will explore the grounds of genocide where nationalism drives to genocide and its implications in the twenty-first century. However, many scholars do not agree with the interpretations of genocide that is led by various conflicts such as historic, religious, ethnicity and many more. Moreover, it will discuss the functionalist and intentionalist and the connections to the contemporary day that links the origins of genocide. Also, it will annotate the statement of Fein of twentieth-century genocide being the “virtual state crime”. In summary, the article will have encountered the causes of genocide and the reasons for various stages which genocide occurred. It will also be understood that the era of modern technology has a great influence in propagating and transmitting communications amongst states and groups more efficiently. Abstrak: Artikel ini akan menyelidiki kondisi mendasar yang memungkinkan terjadinya genosida, menganalisis fakta, memeriksa bagaimana dan mengapa manusia mampu melakukan tindakan kejahatan seperti itu. Sepanjang sejarah banyak intelektual termasuk Raphael Lempkin (1944) yang mendefinisikan istilah genosida. Genosida dipahami sebagai kejahatan paling berat yang dilakukan terhadap kemanusiaan. Tindakan ini dilakukan untuk menghancurkan suatu kelompok etnis, bangsa, ras atau agama secara keseluruhan atau sebagian. Genosida bukan hanya tidak adil, tetapi juga jahat. Genosida adalah pembunuhan massal yang biasanya dilakukan oleh suatu negara atau kelompok, disebabkan oleh konflik dan ketegangan antara berbagai aliran yang berlangsung lama dan menimbulkan kecemasan yang berujung pada pembunuhan massal. Alasan tindakan kejahatan terhadap kemanusiaan tersebut bervariasi, dari orang ke orang - seperti, untuk mendapatkan kekuasaan, keserakahan, pengaruh politik, balas dendam atau alasan agama. karakteristik genosida adalah pembunuhan terhadap warga sipil yang tak berdaya. Selanjutnya akan dijelaskan kasus dan pola genosida yang unik serta pembahasan Stanton mengenai sepuluh tahapan yang menyebabkan suatu negara atau individu melakukan pembunuhan massal. Juga akan dibahas propaganda negatif pemerintah dan kelompok yang menyebabkan perpecahan di antara masyarakat. Terakhir, artikel ini akan menjelajahi dasar genosida di mana nasionalisme mengarah pada genosida dan implikasinya di abad ke-21. Namun, banyak sarjana tidak setuju dengan interpretasi genosida yang dipicu oleh berbagai konflik seperti sejarah, agama, etnis, dan banyak lagi. Selain itu, ini akan membahas fungsionalis dan intensionalis serta kaitannya dengan zaman kontemporer yang menghubungkan asal-usul genosida. Juga, itu akan disertai dengan keterangan dan pernyataan Fein tentang genosida abad ke-20 sebagai